Salmonella Paratyphi A in India - Changing trends in presentation and antibiotic susceptibility - Kulkarni, Sanjay V; Narayan, Arun; Indumathi, Vrithmani Aprameya; Rao, Tejas Suresh; Kempegowda, Punith (Asian Journal of Medical Sciences, 2011)
Objective: Not only has the prevalence of enteric fever due to Salmonella paratyphi A increased over the last decade, there has also been a change in common presenting symptoms and antibiotic sensitivity pattern of these organisms. Knowledge of the existing epidemiology of the disease is essential for a rational approach to treat the same. Hence the present study was done to establish the existing epidemiology of enteric fever due to Salmonella paratyphi A-their common presenting symptoms and antibiotic sensitivity pattern- at our setting. Material & Methods: This prospective study was conducted in MS Ramaiah Hospitals, Bangalore between January 2008 and December 2008. Patients admitted to the hospital with clinical suspicion of enteric fever and whose blood culture grew paratyphi A were included in the study. Common presenting symptoms and signs were recorded in these patients and the sensitivity patterns of the causative organisms were studied. The difference in their response to Ciprofloxacin and Ceftriaxone was studied. The analysis was done using the statistical software package-SPSS Version 16. The difference in the defervescence period was calculated by 2-way Independent two-sample t-test. Results: A total 32 patients were included in the study. Fever and hepatomegaly were the most common symptom and sign among the study subjects. All isolates were susceptible to commonly used antibiotics except for Nalidixic acid. The mean defervescence period was shorter in patients treated with Ceftriaxone as compared to those treated with Ciprofloxacin (p<0.002). Conclusion: We report a change in the presentation and antibiotic sensitivity of paratyphi A infection as compared to existing literature. Ceftriaxone is a better drug as choice as it has shorter defervescence time. Key Words: Salmonella paratyphi A; Ceftriaxone; Ciprofloxacin; Defervescence DOI: 10.3126/ajms.v2i1.3546 Asian Journal of Medical Sciences 2 (2011) 14-17